Chapter Sustainable Innovation: worldwide trends in the scientific production through a bibliometric study - Cataldo, Rosanna (Proceedings e report, 2021)
The scientific production on the Innovation, especially on Sustainable Innovation, has grown in recent years. Various expressions and definitions for sustainability and innovation have been reported in the literature. Sometimes the two concepts are combined and described with one term, Sustainable Innovation. Research on sustainable innovation has grown in popularity due to the need to incorporate sustainability within business practices. The purpose of this study is to investigate the status and the evolution of the scientific studies on this topic and identify the worldwide trends in scientific production over time through a research conducted on the metadata of Web of Science, a database commonly used by researchers. A bibliometric analysis has been developed to analyse a total of 1,511 documents published between 2000 and 2021 in order to discover the research trends in this field and the main dimensions and words related to the term “Sustainable Innovation”.